Effects of Blue-Green Infrastructures on the Microclimate in an Urban Residential Area Under Hot Weather - Cao, Shengyan; Wang, Yafei; Ni, Zhuobiao; Xia, Beicheng (Frontiers in Sustainable Cities, 2022)
With the expansion of cities, the urban population explodes globally, and the thermal environment continues to deteriorate. The studies on urban microclimate have important implications for the construction of green communities and the sustainable development of cities. Various blue-green infrastructures (BGIs) in the urban ecosystem play an important role in regulating urban microclimate and human thermal comfort. This study investigated the current microclimate of a residential area (Chigang community, Guangzhou) under hot weather by carrying out field surveys. Subsequently, a model was established with ENVI-met to simulate the microclimate conditions under different BGIs scenarios. The results showed that adding water bodies can improve the thermal comfort of residential areas. The cooling effect was the best when the water bodies were added dispersedly. In terms of thermal comfort, adding water bodies reduced the heat stress in the surrounding environment. In addition, reducing the existing vegetation heated the study area and reduced humidity. The more dispersed the vegetation, the better the thermal comfort. Vertical greening has better cooling and humidifying effects before noon, whereas it slightly increased the temperature of the study area in the afternoon. Finally, the dispersed vegetation combined with the addition of vertical greening in Chigang community was found to be the optimal design. Under the optimal scenario, the proportion of “neutral” thermal comfort was increased by 1.65%. The results of this study provide references for urban planning and BGI construction.